Effect of feeding a mixture of plants containing secondary metabolites and peppermint oil on rumen fermentation, microbial profile and nutrient utilization in buffaloes - KUMAR, RAVINDRA; KAMRA, D N; AGARWAL, NEETA; CHAUDHARY, L C (The Indian Journal of Animal Sciences, 2011)
A mixture of plants (mix) and peppermint oil (PO) were evaluated in fistulated buffaloes in 3Ã—3 latin square design to study their effect on rumen fermentation, microbial profile, microbial protein synthesis and nutrients utilization. The plant mixture consisted of leaves of mango (Mangifera indica), jamun (Eugenia jambolana), guava (Psidium guajava), seed pulp of harad (Terminalia chebula) and fennel (Foeniculum vulgare) in equal proportions and was fed @ 40 g (dried) /100 kg BW, while peppermint oil was supplemented @ 2 ml/100 kg BW. There was no difference in postprandial changes in pH and total volatile fatty acids in rumen liquor among groups. The proportion of propionate was significantly lower in mix as compared to control and PO supplemented groups. The ammonia nitrogen (mg/dl) was lower in mix fed group as compared to control, whereas, total-N, TCA precipitable-N, activities (IU/mg protein) of carboxy-methylcellulase, xylanase and acetylestrase and protozoa population were similar in all the groups. Real time PCR studies indicated an increase of about 9- and 7-folds in total bacteria and Fibrobater succinogenes populations and a 30-fold decrease in Ruminococcus flavefaciens population with no change in fungal population by mix supplementation. The PO supplementation decreased about 7- and 1.5â€“ folds in fungal and R. flavefaciens populations, whereas about F. succinogenes population showed 6-fold increase as compared to control. The concentrations of purine derivatives in urine were similar in all the groups reflecting similar microbial protein synthesis. The dry matter, TDN and DCP intakes and nutrients digestibility, except that of ether extract were not affected by the feed additives. These results indicated that dietary supplementation of mix and peppermint oil at the present level had no adverse effect on rumen fermentation pattern, microbial protein synthesis and nutrient digestibility in buffaloes.